Establishing key criteria to define and compare models of specialist palliative care: A mixed-methods study using qualitative interviews and Delphi survey. (September 2019) - Firth, Alice M; O'Brien, Suzanne M; Guo, Ping; Seymour, Jane; Richardson, Heather; Bridges, Christopher; Hocaoglu, Mevhibe B; Grande, Gunn; Dzingina, Mendwas; Higginson, Irene J; Murtagh, Fliss EM
Background: Specialist palliative care services have various configurations of staff, processes and interventions, which determine how care is delivered. Currently, there is no consistent way to define and distinguish these different models of care. Aim: To identify the core components that characterise and differentiate existing models of specialist palliative care in the United Kingdom. Design: Mixed-methods study: (1) semi-structured interviews to identify criteria, (2) two-round Delphi study to rank/refine criteria, and (3) structured interviews to test/refine criteria. Setting/participants: Specialist palliative care stakeholders from hospice inpatient, hospital advisory, and community settings. Results: (1)  Semi-structured interviews with 14 clinical leads, from eight UK organisations (five hospice inpatient units, two hospital advisory teams, five community teams), provided 34 preliminary criteria. (2)  Delphi study : Round 1 (54 participants): thirty-four criteria presented, seven removed and seven added. Round 2 (30 participants): these 34 criteria were ranked with the 15 highest ranked criteria, including setting, type of care, size of service, diagnoses, disciplines, mode of care, types of interventions, 'out-of-hours' components (referrals, times, disciplines, mode of care, type of care), external education, use of measures, bereavement follow-up and complex grief provision. (3)  Structured interviews with 21 UK service leads (six hospice inpatients, four hospital advisory and nine community teams) refined the criteria from (1) and (2), and provided four further contextual criteria (team purpose, funding, self-referral acceptance and discharge). Conclusion: In this innovative study, we derive 20 criteria to characterise and differentiate models of specialist palliative care – a major paradigm shift to enable accurate reporting and comparison in practice and research.